Strategi Peningkatan Kepatuhan Wajib Pajak kendaraan Bermotor di kantor Samsat Painan - Nora Susanti; Silvia Cania; Nilmadesri Rosya (Universitas Negeri Padang, 2020)
This research is more towards a strategy in increasing motor vehicle taxpayer compliance in the Pesisir Selatan. Respondents in this study amounted to 75 people who are motor vehicle taxpayers in the Pesisir Selatan Regency and the sampling was done by accidental sampling technique. This research method uses multiple regression analysis and hypothesis testing with a t-test and f test. Compliance with motor vehicle taxpayers in the Pesisir Selatan is influenced by taxpayer awareness and service quality. Partially found that awareness of taxpayers and service quality affects the compliance of motor vehicle taxpayers. And it was found that service quality has the most influence in increasing taxpayer compliance. This means that by increasing the quality of service from the One Roof System office at Painan, it can increase the amount of regional revenue from motorized vehicle ownership.Keywords: compliance of motor vehicle taxpayers, taxpayer awareness, service quality